Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

« Dialogue santé » une consultation historique auprès des communautés francophones de l’Ontario - Dallaire, Hélène; Rail, Geneviève (Reflets, 1995)

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)
fs-ref-orig: Duguay, B. (2007). Initiatives intergénérationnelles en santé. Rapport final. La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français. fs-code-orig: Duguay-2007a

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Le renforcement des capacités : déclin ou levier à l'amélioration de la qualité de vie des aînés ? Le cas de St-Wilfred et de Robertville en Acadie - Simard, Majella (Reflets, 2022)
Le vieillissement de la population représente une réalité complexe. Bien que les causes attribuables à ce phénomène fassent consensus auprès des chercheurs, ses manifestations et ses conséquences diffèrent d’un endroit à l’autre. Dès lors, le rythme et l’intensité du vieillissement ainsi que les moyens déployés par les différents acteurs sociaux pour en atténuer les effets et améliorer les conditions de vie des aînés se manifestent aussi différemment selon les milieux géographiques. Pour diverses raisons liées à la démographie et à la géographie, les défis liés à la gestion du vieillissement tendent à se manifester avec plus d’acuité en milieu minoritaire francophone. L’objectif de cet article consiste à examiner la contribution du modèle de renforcement des capacités à l’amélioration de la qualité de vie des aînés vivant au sein de deux localités sises en milieu rural minoritaire francophone. L’étude de cas exploratoire couplée à l’approche des représentations sociales des acteurs a été retenue comme méthode d’analyse. Des entrevues semi-dirigées effectuées auprès d’intervenants locaux et communautaires ainsi que la tenue de deux groupes de discussion constituent les instruments d’analyse qui ont été mobilisés. Bien que les résultats de notre analyse révèlent le rôle d’avant-plan de la résilience, du réseautage, de la vie relationnelle, du sentiment identitaire et du capital social dans l’amélioration de la qualité de vie des aînés, ces composantes relatives à leurs facultés s’avéreraient insuffisantes afin de favoriser un vieillissement sur place, d’où la nécessité de déployer en amont une politique territoriale du vieillissement. Mots-clés : vieillissement, milieu rural, renforcement des capacités, qualité de vie, Acadie